Identifying Stroke Caregivers’ Coping Strategies: The Smile that has Struggled through the Tears-A Mixed-Method Research Approach - Md Mizanur Rahman; Norliza binti Suut; Zabidah binti Putit; Mohamad Taha Arif; Asri bin Said; Mohd Raili bin Suhaili; Mohd Fadzillah; Zainab binti Tambi; Ling How Kee (Ibn Sina Medical College, 2025)
Indexed by Scopus